Application of Food Hygiene and Sanitation Principles on Food Handlers at The Madang Campus Canteen, Faculty of Medicine University of Sriwijaya - Ellysa Carolinna; Ardesy Melizah Kurniati; Emma Novita; Iche Andriyani Liberty; Mariana Mariana (Majalah Kedokteran Sriwijaya, 2022)
A food handler must know information related to hygiene, sanitation, and food nutrition and maintain food health and hygiene so that consumers can avoid the dangers of food or drink that does not meet health requirements. Until now, there are no guidelines that stipulate regulations regarding the provision of safe and hygienic food and beverages in canteens. The design used in this research is qualitative research with a case study method. The sampling method used was the purposive sampling technique. The research data were obtained from 1 key informant, five primary informants, and four supporting informants who had met the inclusion and exclusion criteria. The data analysis method used is content analysis. The results of this study are the application of food hygiene and sanitation principles has been carried out by food handlers. Still, there are some discrepancies between the theory and applicable rules. This study concludes that applying the principles of hygiene and sanitation carried out by food handlers in the Madang Campus canteen is not by the appropriate theories and rules.